Pathogenesis-related protein 10 in resistance to biotic stress: progress in elucidating functions, regulation and modes of action - Lopes, Natasha dos Santos; Santos, Ariana Silva; de Novais, Diogo Pereira Silva; Pirovani, Carlos Priminho; Micheli, Fabienne (Frontiers in Plant Science, 2023)
Introduction The Family of pathogenesis-related proteins 10 (PR-10) is widely distributed in the plant kingdom. PR-10 are multifunctional proteins, constitutively expressed in all plant tissues, playing a role in growth and development or being induced in stress situations. Several studies have investigated the preponderant role of PR-10 in plant defense against biotic stresses; however, little is known about the mechanisms of action of these proteins. This is the first systematic review conducted to gather information on the subject and to reveal the possible mechanisms of action that PR-10 perform. Methods Therefore, three databases were used for the article search: PubMed, Web of Science, and Scopus. To avoid bias, a protocol with inclusion and exclusion criteria was prepared. In total, 216 articles related to the proposed objective of this study were selected. Results The participation of PR-10 was revealed in the plant’s defense against several stressor agents such as viruses, bacteria, fungi, oomycetes, nematodes and insects, and studies involving fungi and bacteria were predominant in the selected articles. Studies with combined techniques showed a compilation of relevant information about PR-10 in biotic stress that collaborate with the understanding of the mechanisms of action of these molecules. The up-regulation of PR-10 was predominant under different conditions of biotic stress, in addition to being more expressive in resistant varieties both at the transcriptional and translational level. Discussion Biological models that have been proposed reveal an intrinsic network of molecular interactions involving the modes of action of PR-10. These include hormonal pathways, transcription factors, physical interactions with effector proteins or pattern recognition receptors and other molecules involved with the plant’s defense system. Conclusion The molecular networks involving PR-10 reveal how the plant’s defense response is mediated, either to trigger susceptibility or, based on data systematized in this review, more frequently, to have plant resistance to the disease.